Electric Motor Efficiency: A Key Factor in Tackling Air Pollution - Fadhilah, Nurul (Oshada, 2024)
In the face of serious air pollution threats from conventional motor vehicles, electric motors have emerged as a key pillar in efforts to achieve clean air and optimal health. This article explores the concept of electric motor efficiency and its crucial role in tackling air pollution that can impact health. Electric motors not only eliminate exhaust emissions, but also offer higher energy conversion efficiency, reducing energy losses during operation. By referring to leading sources such as the International Energy Agency (IEA) and the American Council for an Energy-Efficient Economy (ACEEE), we can understand the positive impact of electric motors on air quality. Although some challenges, such as battery range limitations, need to be overcome, the efficiency of electric motors remains the key to paving the way for sustainable solutions that significantly reduce the impact of air pollution. Air pollution has a serious impact on human health. Long-term and short-term exposure to air pollutants can cause various serious health problems such as respiratory tract disorders, cardiovascular disease, and others.